A Critical Reflection of Phenomenon on Commodification of Body in Capitalist Economy Era - Edu, Ambros Leonagung (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
This paper presents some cases of abuse on the body seen at places of work, marriage life, and even food.It is a reflection on the phenomenon of looting, harassment and commodification of the body in the currentcapitalist era. Although it seems like a philosopical description, but the end remains a social fact descriptions.Facts about condition of the body as something sacred and holy, now it has been reduced andtransformed as a place to satisfy erotic and material matters.Keywords: body, commodification, economy